Behavioral Inefficiency on a Risky Decision-Making Task in Adulthood after Adolescent Intermittent Ethanol Exposure in Rats - Miller, Kelsey M. (Sci Rep, 2017)
Adolescence is a period of development in neural circuits that are critical for adult functioning. There is a relationship between alcohol exposure and risky decision-making, though the enduring effects of adolescent ethanol exposure on risky decision-making in adulthood have not been fully explored. Studies using positive reinforcement have shown that adolescent intermittent ethanol (AIE) exposure results in higher levels of risky decision-making in adulthood, but the effects of AIE on punishment-mediated decision-making have not been explored. Adolescent rats were exposed to AIE or saline vehicle across a 16-day period, and then allowed to mature into adulthood. They were then trained to lever press for food reward and were assessed for risky decision-making by pairing increased levels of food reward with the probability of footshock punishment. AIE did not alter punishment-mediated risky decision-making. However, it did result in a significant increase in the delay to lever pressing. This finding is consistent with previous reports, using other behavioral tasks, which show decreased behavioral efficiency in adulthood after AIE. These findings indicate that AIE increases behavioral inefficiency, but not punishment-mediated risk-taking, in adulthood. Thus they contribute to a more nuanced understanding of the long-term effects of AIE on adult behavior.